Penguatan Dakwah Badan Wakaf Indonesia Melalui Pembinaan Nazhir - Sabirin, Yoga Basyiril; Zen, Muhammad; Fatmawati, Fatmawati (Jurnal Al-Hikmah: Jurnal Dakwah, 2024)
Waqf plays an important role in empowering the ummah, whether economically, socially, or educationally. Effective waqf management depends on the quality of the nazir, who is responsible for waqf assets. The Indonesian Waqf Board (BWI) plays an important role in nazir coaching to ensure productive waqf management. This study aims to examine BWI's nazir coaching strategy and its impact on community empowerment. With a literature study-based qualitative approach, this research analyzes coaching programs such as administrative, managerial, and spiritual training. The results show that BWI's coaching has succeeded in improving the capacity of nazir in waqf management, especially in terms of managerial and leadership. However, challenges related to the diversity of nazir backgrounds and limited resources still exist. Although technical coaching is sufficient, social and spiritual aspects need to be improved. This study concludes that a more holistic and adaptive coaching strategy is needed to support sustainable waqf-based philanthropy.[Wakaf memiliki peran penting dalam pemberdayaan umat, baik secara ekonomi, sosial, maupun pendidikan. Pengelolaan wakaf yang efektif bergantung pada kualitas nazhir, yang bertanggung jawab atas aset wakaf. Badan Wakaf Indonesia (BWI) memainkan peran penting dalam pembinaan nazhir untuk memastikan pengelolaan wakaf yang produktif. Penelitian ini bertujuan untuk mengkaji strategi pembinaan nazhir oleh BWI dan dampaknya terhadap pemberdayaan umat. Dengan pendekatan kualitatif berbasis studi pustaka, penelitian ini menganalisis program pembinaan seperti pelatihan administratif, manajerial, dan spiritual. Hasil penelitian menunjukkan bahwa pembinaan BWI berhasil meningkatkan kapasitas nazhir dalam pengelolaan wakaf, terutama dalam hal manajerial dan kepemimpinan. Namun, tantangan terkait keberagaman latar belakang nazhir dan keterbatasan sumber daya masih ada. Meskipun pembinaan teknis sudah cukup, aspek sosial dan spiritual perlu ditingkatkan. Penelitian ini menyimpulkan bahwa strategi pembinaan yang lebih holistik dan adaptif diperlukan untuk mendukung filantropi berbasis wakaf yang berkelanjutan].